Supporting partnership sourcing in Northern Ireland through advanced technology - McGloin, Eileen; Grant, Caroline
The paper concentrates on the way in which organisations can exploit advanced technologies and concepts, such as electronic communication, to support strategic alliances with trading partners.
To survive in today's global marketplace, businesses need to be able to deliver products on time, maintain market credibility and introduce new products and services faster than competitors. The Northern Ireland economy has endured an economic crisis since the 1970s: there has been high unemployment and difficulty in attracting inward investment due to political considerations. The emergence of small to medium sized enterprises (SMEs) seems to be one of the solutions to shaping the economy in this geographic region (Northern Ireland Structural Funds Plan, 1993). The opening section of this paper examines modern manufacturing philosophy and the economic environment within which SMEs exist in Northern Ireland. SMEs need a solid strategy for achieving and maintaining a competitive advantage. One proven strategy is based on the Japanese practice of partnership sourcing. This paper proposes that concepts such as electronic commerce and Internet technology can facilitate and support such alliances between trading partners. Evidence is mounting that conducting business electronically has already changed the way business is carried out in some industries. Advanced technology can shrink geographical distance and restructure supply chains, enhancing industrial alliances and enabling efficient timely exchange of information between purchasers and suppliers. This paper surmises that the integration of advanced technology and partnership sourcing will offer SMEs unprecedented opportunities within the global marketplace of the future.
Keywords: Partnership sourcing--Northern Ireland; Advanced technology